Money and the economy - Klein, John J. (New York: Harcourt Brace Jovanovich, 1974)
This book is designed to fill the needs of the junior-senior course in money and banking. The book pro vides a basic but rigorous exposition of financial institutions, theoretical analysis, and economic policy. It is divided into five parts. Part I, Money and Private Institutions. Part II, Money and Government. Part III, Financial Markets and Portfolio Decisions.. Part IV, Money and Aggregate Economic Activity. Part V, Money and Economic Policy: International and Domestic Policies.
Includes bibliographies.
rpm 26/04/2018
Loans
Keywords: Monetary policy